Implementation of the Public Policy Strategy Model in Elementary School Education - Muhammad Al Mighwar; Desyana Nurlatipah (ATTAQWA: Jurnal Pendidikan Islam dan Anak Usia Dini, 2023)
This  study   aims   to   observe   and   describe   various   phenomena  that   arise   during   the implementation of  the  strategic  model of  basic  education public  policy. Using a  qualitative descriptive approach, this research analyzes the supporting factors and inhibiting factors in the implementation of basic education, and it is found that teachers  need to know more about the factors that support and hinder the implementation of education policies in elementary schools, principals, teachers, service education and society A joint effort is needed to implement  it so that  it  can be provided to meet  the appropriate  needs of regular students and children with special needs to improve the quality  and potential  of primary school education services.